Leo Tolstoy : Resident and Stranger - Gustafson, Richard F. (Book collections on Project MUSE., 2014)
Much of what was central to Tolstoy seems embarrassing to Western and Soviet critics, points out Richard Gustafson in his absorbing argument for the predominance of Tolstoy's religious viewpoint in all his writings. Received opinion says that there are two Tolstoys, the pre-conversion artist and the post-conversion religious thinker and prophet, but Professor Gustafson argues convincingly that the man is not two, but one. Originally published in 1989. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print bo.